Lean Innovation A Fast Path from Knowledge to Value - Sonnenberg, Henrik; Sehested, Claus; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
Within manufacturing, Lean has lead to significant results throughout the world. But what happens when Lean meets Innovation? Is the needed creativity destroyed, or can Lean make the results of the organization even better? In Lean Innovation, Claus Sehested and Henrik Sonnenberg reveal how a managed iteration between creativity and effectiveness can ensure that the visions of top management are realized through the innovation processes. Lean can elevate the innovation processes to a new level where they become a true strategic differentiator. The authors address the key challenges facing leaders of knowledge organizations, and present a number of principles which they can use to bring more leadership into the innovation work. They also discuss methods which can increase result focus and continuous learning in the core innovation processes. The book contains specific and practical examples from five companies who started on a Lean Innovation journey. Innovation Insights from Apple, Google, Toyota, IDEO and others are also included.
Part I Understanding the Background -- Introduction -- Chapter 1 The Potential of Lean Innovation -- Part II Understanding the Fundamentals -- Chapter 2 Understanding Innovation -- Chapter 3 Understanding Lean Innovation -- Part III Achieving Success with Lean Innovation -- Chapter 4 Releasing the Potential for Innovation -- Chapter 5 Active and Visible Management -- Chapter 6 Realizing Your Strategy through Portfolio Management -- Chapter 7 Projects Create Customer Value - Chapter 8 The Role of Project Support in Innovation -- Part IV Starting the Development Process -- Chapter 9 Fast from Knowledge to Value -- Postscript Fueled by a Dream.
Keywords: Economics; Industrial management; Business logistics; Technology; Economics/Management Science; Management/Business for Professionals; Technology Management; Production/Logistics.